ANALYSIS OF DEXAMETASONE LEVELS IN HERBAL WEIGHT GAIN MEDICINE CIRCULATING IN BUKITTINGGI CITY USING UV-VIS SPECTROPHOTOMETRY - Fitriani, Oryza Sativa; Khaidir, Muhammad; Hasanah, Rizqa; Rahmadasmi, Nola; Andika, Miming (HUMAN CARE JOURNAL, 2025)
Chemical drugs are chemical substances added to traditional medicines or herbal medicines to strengthen the indications. One of the chemical drugs that is often added to herbal medicines is dexamethasone. With the presence of dexamethasone content that is intentionally added to herbal medicines, it can increase the weight of consumers who consume the herbal medicine. Dexamethasone in long-term use can cause unwanted hormonal effects, namely a series of changes called iatrogenic Cushing's Syndrome (moon face) and osteoporosis. This study aims to identify the chemical drug dexamethasone in weight-gaining herbal medicines sold in the city of Bukittinggi using purposive sampling techniques and analyzing its levels. The research method was carried out using UV-Vis spectrophotometry. The results of the study showed that there were 2 samples of herbal weight gain medicines that positively contained dexamethasone with a concentration of 1.9771% in herbal medicine 2 and 0.2092% in herbal medicine 7. In conclusion, out of 10 herbal weight gain medicines sold in Bukittinggi City, there were 2 herbal medicine samples that contained the chemical drug dexamethasone.